Transgresja i literatura - Pertek, Grzegorz (Wydawnictwo Naukowe UAM, 2014)
The author of this article attempts to redefine the category of transgression. By preparing a preliminary typology of the existing uses of this concept, he puts forward the hypothesis that, on the one hand, transgression can be identified with (is synonymous with) going beyond the limit of something, and on the other hand, it can be equated with the constant conflict between its empirical and linguistic dimensions as well as its thematization and formalization. The author proposes to define transgression as the act of setting/removing a certain limit. This definition overcomes the above-mentioned difficulties because it not only has an ambiguous aspect (undecidability), i.e. both a positive (construction) and a negative (destruction) dimension, but it also pushes the issues related to transgression into the domain of negotiations, i.e. interactions with the reader (reception, tradition and criticism), from which it derives its inventive potential.
Transgression and literature